The Impact of Short-Form Video Content on Brand Engagement and Purchase Intention Among Generation Z - Muhammad Iqbal; Dimas Perdana Oskar; Andre Ilyas (Journal of Management and Social Sciences, 2026)
This study aims to investigate the impact of short-form video content on brand engagement and purchase intention among Generation Z in South Sumatra. In today’s fast-paced digital era, short-form video content promoted through social media platforms such as TikTok, Instagram Reels, and YouTube Shorts has become a highly effective marketing tool. This study employs a quantitative approach using a survey method, involving 245 respondents aged 18 to 24 years who are active consumers of short-form video content. Data were collected through a questionnaire measured using a 5-point Likert scale, covering variables such as short-form video content, brand engagement, and purchase intention. The results indicate that entertaining, informative, and authentic short-form videos significantly influence brand engagement, which in turn impacts consumer purchase intention. Furthermore, brand engagement was found to mediate the relationship between short-form video content and purchase intention. Dimensions of short-form video content, such as entertainment value, informative content, and authenticity, play an important role in attracting attention and enhancing consumer engagement. These findings provide practical insights for marketers to design more effective marketing strategies, especially in reaching Generation Z consumers who tend to be more selective in consuming content.